Discriminative predation: Simultaneous and sequential encounter experiments - C. D. BEATTY, D.W.FRANKS (Current Zoology, 2012)
There are many situations in which the ability of animals to distinguish between two similar looking objects can have significant selective consequences. For example, the objects that require discrimination may be edible versus defended prey, predators versus non-predators, or mates of varying quality. Working from the premise that there are situations in which discrimination may be more or less successful, we hypothesized that individuals find it more difficult to distinguish between stimuli when they encounter them sequentially rather than simultaneously. Our study has wide biological and psychological implications from the perspective of signal perception, signal evolution, and discrimination, and could apply to any system where individuals are making relative judgments or choices between two or more stimuli or signals. While this is a general principle that might seem intuitive, it has not been experimentally tested in this context, and is often not considered in the design of models or experiments, or in the interpretation of a wide range of studies. Our study is different from previous studies in psychology in that a) the level of similarity of stimuli are gradually varied to obtain selection gradients, and b) we discuss the implications of our study for specific areas in ecology, such as the level of perfection of mimicry in predator-prey systems. Our experiments provide evidence that it is indeed more difficult to distinguish between stimuli – and to learn to distinguish between stimuli – when they are encountered sequentially rather than simultaneously, even if the intervening time interval is short [Current Zoology 58 (4): 649–657, 2012].